Uncovering psychobehavioural implications of SARS‐CoV‐2 infection in Iran. Issue 6 (10th July 2020) - Wong, Li Ping; Alias, Haridah; Danaee, Mahmoud; Ziaee, Masood; Abedi, Farshid; Ziaee, Arash; Mohajer, Samira; HajiAliBeigloo, Reza; Nia, Mohammad Namazi; Jamei, Fateme; Mazlom, Seyed Reza
Abstract: Iran is the country in Western Asia most impacted by the COVID‐19 outbreak. A survey was conducted among the general public in Iran aimed at investigating psychobehavioural issues related to the COVID‐19 outbreak, namely (a) barriers to preventive measures against SARS‐CoV‐2 infection; (b) negative emotions towards SARS‐CoV‐2 infection; and (c) anxiety levels among the general public in Iran. A cross‐sectional, web‐based survey using an online questionnaire was carried out between 16 March and 1 April 2020. The six‐item version of the State‐Trait Anxiety Inventory (STAI‐6) was used to assess anxiety levels. A total of 1, 789 complete responses were received. Nearly 60% reported having difficulty in wearing a face mask to protect against SARS‐CoV‐2 infection. The mean and standard deviation ( SD ) for the total prevention barrier score was 35.8 ( SD ± 7.1; range 18–68) out of a possible score of 72. Male respondents [odds ratio (OR) = 1.25; 95% confidence interval (CI) 1.03–1.51] and respondents who perceived their health status as poor/fair (OR = 1.49; 95% CI 1.31–1.82) were predictors of high prevention barriers. Negative emotions such as fear (74.6%) followed by depression (43.4%) and stigma (23.0%) associated with SARS‐CoV‐2 infection were reported. Respondents who perceived their health as poor/fair (OR = 2.19; 95% CI 1.57–3.04) reported a higher likelihood of having higher negative emotions. Findings on anxiety level revealed 68.0% (95% CI 65.8–70.1) reported moderate to severe anxiety. Respondents who perceived their health as poor/fair (OR = 3.46; 95% CI 12.22–5.40) and who were females (OR = 1.91; 95% CI 1.55–2.36) were predictors of moderate to severe anxiety. In conclusion, psychobehavioural interventions are needed to facilitate management and control of the COVID‐19 outbreak.